50. výročí české integrální antropologie - Mácha, Karel; Troníček, Chrudoš; Stuchlík, Milan (Lidé města, 2016)
Fifty years ago, in December 1966, the Czech Integral Anthropology section of the Czechoslovak Anthropological Society was officially founded. This section represented one of the most significant – although, in the long term, not successful – attempts of implementing the Anglo-American approach to general anthropology in the Czech academic milieu. The Czech Integral Anthropology section underwent a fairly dynamic, albeit, thanks to external forces, short-lived development (it only functioned in its original form until the beginning of the 1970s), and we can characterise it at least as an attempt to “gather together” various anthropologically oriented tendencies in the social sciences, humanities, and biological sciences, as well as an attempt to integrate their findings and approaches. In Mácha‘s intentions, it was to serve as a preparation for the complex studies of man that would achieve international renown, whereas the goals of his colleagues were usually more humble, for example, “merely” presenting the newest findings of Western science to the Czech academic sphere, leading towards its greater engagement in international discussions. We commemorate the fiftieth anniversary of the foundation of the Czech Integral Anthropology section with the series of several conceptual texts from the low-circulation and today practically unknown volume Sborník prací k otázkám integrální antropologie (Collection of Texts on the Issues of Integral Anthropology, 1968), authored by philosopher Karel Mácha, biological anthropologist Chrudoš Troníček, and social anthropologist Milan Stuchlík.